Problematyka wdrożenia rachunku kosztów jakości w przedsiębiorstwie - Zuchewicz, Joanna (The Problem of Quality Costing Implementation in an Enterprise, 2006)
The Problem of Quality Costing Implementation in an Enterprise
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 441-447